Full quantum simulation of Shockley–Read–Hall recombination in p-i-n and tunnel diodes. (December 2022) - Pilotto, A.; Dollfus, P.; Saint-Martin, J.; Pala, M.
Abstract: We have included Shockley–Read–Hall (SRH) generation/recombination in Non-equilibrium Green's function (NEGF) calculations via a multiphonon relaxation model. The model has been used to study how the presence of defects affects the current–voltage characteristics of GaAs p-i-n diodes, and of an InGaAs tunnel diode. Regarding p-i-n diodes, we show that SRH generation/recombination is responsible for ideality factors approaching the theoretical value of two in the forward bias regime, while in reverse bias the recombination current density varies slowly with the applied voltage. In all the considered cases, the defects located in the center of the active region proved to be the most effective in allowing trap-assisted tunneling from the valence to the conduction band. Finally, the inclusion of SRH recombination in NEGF simulations of Esaki tunnel diodes permits to predict a realistic degradation of the peak-to-valley current ratio. Highlights: We have included SRH in NEGF calculations via a multiphonon relaxation model. SRH mostly occurs at defects in the center of the active region of p-i-n diodes. Band bending in thin diodes enhances SRH. Ideality factors can be larger than two. SRH degrades the peak-to-valley current ratio of Esaki diodes.